AI-28 HLA-DR3 restricted responses to SMD, a lupus-related antigen provide insights to the origin of lupus-related autoantibodies and the unique features of the targeted antigens. (31st August 2016) - Fu, Shu Man; Zhao, Zhenhuan; Ren, Jiling; Dai, Chao; Gaskin, Felicia
Abstract : Background: The presence of complex autoantibodies (auto-Abs) is a hallmark of SLE. The most cited hypotheses for their origin are the "B cell epitope mimicry hypothesis between SmB and EBV" and the "particle hypothesis". Neither is adequate to explain the characteristics of SLE–related Abs. Our studies showed that HLA-DR3 and DR2 transgenic mice in contrast to DR4 respond well to SmD and Ro60 with DR3 mice being the best responders. In addition, certain bacterial mimics of SmD and Ro60 T cell epitopes were shown to induce auto-Abs to SnRNP and Ro60/La. Materials and methods: T cell epitope mapping was done by the generation and characterisation of T-T hybridomas to SmD and Ro60 and their 15 mers. Antibody specificities to SLE-related antigens (Ags) and their peptides were done by ELISA. Results: At least seven SmD core T cell epitopes were identified. They have no sequence homology. 18 of reactive T-T hybridomas used multiple TCRα and TCRβ. Bioinformatics analysis identified more than 10000 potential bacterial mimic peptides with many from commensal bacteria. The binding affinities of the SmD T epitopes were in the medium range among all the relevant mimics. Selected mimic peptides showed that only those with medium binding affinities stimulated related T-T hybridomas to the SmD peptides and only they were able to stimulate Ab responses in patterns similar to that induced by the related SmD peptide. A significant number of T-T hybridomas were reactive with multiple T cell epitopes within the SmD molecules. Some of these hybridomas also were reactive with SmD, SmB and/or A-protein within the snRNP particles and Ro60. In addition, the bacterial T cell mimic peptides often shared B cell epitopes with the related SmD peptide. Also healthy DR3 + blood donors had significantly higher Ab titers against SmD. Similar results were obtained in the Ro60/La system. Conclusions: Autoreactive TCRs are part of the normal repertoire that are positively selected for host defense against microbial agents. The presence of multiple intra- and inter-molecular T and B cell epitopes are characteristic of SLE-related auto-Ags. These characteristics provide a scenario for the inevitability of the presence of auto-Ab and autoreactive-T cells in healthy individuals with susceptible HLA-D regions and provide a mechanism for B cell epitope spreading in SLE. SLE-related Abs are the results of our reaction to exposure to commensal and/or pathogenic microbes. Innate immunity plays an amplifying role. These observations provide the rationale to target microbiome and both adaptive and innate immunities in the treatment of SLE.